PENINGKATAN HASIL BELAJAR SISWA DENGAN METODE KOOPERATIF TIPE GROUP INVESTIGATION MATA PELAJARAN PKN SD 167648 KOTA TEBING TINGGI - Sabaria Haloho (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2015)
ABSTRACT This purposes of this research is to improve learning result on PKn subject  through cooperative method group investigation type. This classroom action research conducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class IV, SDN 167648 Tebing Tinggi which amounted to 33 students. This study used a qualitative descriptive analysis technique. The results showed that the use of the cooperative method group investigation typeof PKn subjects can improve student learning result characterized by increased mastery learning students, namely pre-cycle (66,67%), the first cycle (72,72%), cycle II (90,90 %) and complete learn the clasical equal to 90,90 %.   Key word : cooperative, group investigation, learning result